PENDAMPINGAN DALAM PENGUATAN MATERI MODERASI BERAGAMA BAGI SANTRI ISLAMIC BOARDING SCHOOL PADEPOKAN KYAI MUDRIKAH KEMBANG KUNING PAMEKASAN - Listiana, Heni; Muhlis, Achmad; Nada, Zilfania Qathrun (CV. Jendela Gagasan, 2025)
Religious moderation is a crucial concept in maintaining harmony and tolerance in society. However, the lack of understanding and implementation of religious moderation among students often poses challenges, particularly at IBS Padepokan Kyai Mudrikah Kembang Kuning, Pamekasan. This situation can lead to potential intolerance and radicalism, which contradicts the values of Islam as rahmatan lil 'alamin (a mercy to all creations). This article aims to describe the mentoring process in strengthening the material of religious moderation for students at IBS Padepokan Kyai Mudrikah Kembang Kuning, Pamekasan. The ultimate goal is to enhance the understanding and application of religious moderation so that the students can become agents of change, promoting values of tolerance and harmony within the community. The mentoring method involves a qualitative approach, including direct observation, in-depth interviews, and focused group discussions (FGDs) with students and educators. The mentoring program is structured in several stages, starting from the introduction of concepts, discussion of real-life cases, to the implementation of moderation values in the students' daily lives. The mentoring conducted shows a significant increase in the understanding and attitude towards religious moderation among the students. They have become more capable of understanding the importance of tolerance, appreciating differences, and avoiding extreme attitudes. Additionally, this program has successfully raised critical awareness among students about contemporary religious issues that are often used to divide the ummah (Muslim community). The mentoring in strengthening the material of religious moderation at IBS Padepokan Kyai Mudrikah Kembang Kuning, Pamekasan, has successfully enhanced the understanding and moderate attitudes among students. This program is effective in preventing potential intolerance and radicalism, and in shaping students with a strong commitment to the values of Islam as rahmatan lil 'alamin. Consequently, the students are expected to become agents of change who contribute positively to harmony and tolerance in society.